2021
DOI: 10.3390/biom11040522
|View full text |Cite
|
Sign up to set email alerts
|

Alarming Cargo: The Role of Exosomes in Trauma-Induced Inflammation

Abstract: Severe polytraumatic injury initiates a robust immune response. Broad immune dysfunction in patients with such injuries has been well-documented; however, early biomarkers of immune dysfunction post-injury, which are critical for comprehensive intervention and can predict the clinical course of patients, have not been reported. Current circulating markers such as IL-6 and IL-10 are broad, non-specific, and lag behind the clinical course of patients. General blockade of the inflammatory response is detrimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 249 publications
(410 reference statements)
0
21
0
Order By: Relevance
“…52,53 The in vivo findings indicate that HACM preserved with the polyampholyte cryoprotectant protects properties of HACM that appear to promote the healing of delayed wounds in a diabetic mouse macrophages also secrete high levels of PDGF, which has been shown to promote angiogenesis. 54 Biomechanical measurements of the healed tissue indicated that polyampholyte preserved HACM had better integrity, and when compared with the untreated wounds, it was statistically significant ( p < 0.05). From the perspective of wound closure, the preserved HACM appear to promote the healing of diabetic mouse wounds, but additional samples will be required to reach statistical significance.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…52,53 The in vivo findings indicate that HACM preserved with the polyampholyte cryoprotectant protects properties of HACM that appear to promote the healing of delayed wounds in a diabetic mouse macrophages also secrete high levels of PDGF, which has been shown to promote angiogenesis. 54 Biomechanical measurements of the healed tissue indicated that polyampholyte preserved HACM had better integrity, and when compared with the untreated wounds, it was statistically significant ( p < 0.05). From the perspective of wound closure, the preserved HACM appear to promote the healing of diabetic mouse wounds, but additional samples will be required to reach statistical significance.…”
Section: Discussionmentioning
confidence: 90%
“…M2a macrophages play a critical role in ECM formation, which is a prerequisite for the proliferative phase of wound healing. M2a macrophages also secrete high levels of PDGF, which has been shown to promote angiogenesis 54 . Biomechanical measurements of the healed tissue indicated that polyampholyte preserved HACM had better integrity, and when compared with the untreated wounds, it was statistically significant ( p < 0.05).…”
Section: Discussionmentioning
confidence: 96%
“…Extracellular vesicles carry cargos, such as lipids, proteins, DNAs, and RNAs, so as to influence remote organ functions and act on traumatic injuries, serving as biomarkers of inflammatory-based diseases and clinical sequelae (44). Massive studies elucidated that EVs have potential therapeutic effects on alleviating IVD degeneration (45)(46)(47), and PRP is known to provide a protective and reparative role in IVD and diseases related to IVD degeneration (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, exosomes facilitate communication between immune cells and also activate and recruit other immune cells to the site of injury or infection. This could be vital in the immediate postoperative period, as the immune response is a key factor in preventing tissue infection and assisting proper wound healing [ 168 ]. Conclusively, the exosomes released after trauma or surgery appear to play a significant role in healing.…”
Section: Relationship Between Exosomes Biogenesis and Actions With Dr...mentioning
confidence: 99%